Centre for transportation studies: centre activities from 1990 to 2006 - Fan, Henry Shing Leung (2008)
On 19 November 1990, the Council of Nanyang Technological Institute [reconstituted as Nanyang Technological University in 1991] directed the University to establish the Centre for Transportation Studies (CTS) to serve Singapore and the region in the field of transportation. The role of CTS, as directed by the Council, is to fulfil this mission through activities in Research and Development, Education and Training, and Technology Exchange. The funding provided under this project is for the initial set-up of CTS. It covered the purchase of furniture, office equipment, computers, printers, software packages and other equipment to facilitate the conduct of Centre activities. CTS has operated as a self-financing centre supported by income generated from carrying out contract research, conducting short courses and organising conferences. Up to the start of 2006, the Centre has carried out over 30 projects, with more than 85% of these being contract studies funded by external parties. In education and training, CTS offers a formal Graduate Diploma programme in Airport Engineering and continuing education short courses. The Diploma programme, a joint effort between NTU and the Civil Aviation Authority of Singapore, is widely recognized in the aviation community as a programme of excellence in airport engineering training.